Performance evaluation of using water-based nanofluids as coolants in the gas cooler of a transcritical CO2 refrigerant system - Sarkar J. (My University, 2025)
This study explores the possibility of the performance improvement of the gas cooler as well as a transcritical carbon dioxide refrigeration system using Al2O3, TiO2, SiO2, and CuO nanofluids as coolants in the double-tube gas cooler through theoretical analyses. Effects of various operating parameters (CO2 pressure in the gas cooler, mass flow rate, and particle volume fraction) are studied as well. The gas cooler effectiveness, cooling capacity, and COP can be improved by using nanofluid as coolant in a double-tube gas cooler of CO2 cycle with negligible effect on pumping power. The CO2 system yields the best performance using Al2O3-H2O as a coolant in a double-tube gas cooler followed by TiO2-H2O, SiO2-H2O, and CuO-H2O. With Al2O3-H2O nanofluid, the maximum cooling COP improvement of a transcritical CO2 system is 25.4%, whereas that with TiO2-H2O is 23.8%, with SiO2-H2O is 23.1%, and with CuO-H2O is 20.2% for the studied ranges of this study. The present analysis reveals that the performance of the transcritical CO2 refrigeration cycle can be improved by using nanofluid as coolant in a double-tube gas cooler. Alternately, component size and cost can be reduced by using a nanofluid. © 2013 by Begell House, Inc.